Analisis Strategi Komunikasi Pemasaran Bisnis B2B Jasa Kalibrasi PT Mandiri Global Akurasi - Riki Khoerul Anwar; Dani Setiadarma (Indo Publishing, 2026)
This study analyzes the development of marketing communication strategies to build brand awareness at PT Mandiri Global Akurasi, a B2B calibration services company facing a sharp decline in revenue (69.6% in 2024 and 45% in 2025) and unstable client turnover. Using a constructivist paradigm with a qualitative case study approach, this study explores the subjective understandings of marketing managers, salespeople, administrative staff, and clients regarding their marketing communication practices. The findings reveal fundamental differences in the meaning of marketing communication. Management constructs it as a short-term acquisition instrument with quantitative targets (20 calls/emails per day). Clients interpret it as proof of professionalism and a foundation for long-term trust, with indicators such as speed of response, technical clarity, and post-sales attention. The CRM Practice Manual reflects the construction that client data is understood as administrative, not strategic assets. The process of constructing reality occurs through daily interactions: when salespeople explain calibration procedures, management interprets it as